2018
DOI: 10.5603/demj.2018.0028
|View full text |Cite
|
Sign up to set email alerts
|

The place of TrueCPR feedback device in cardiopulmonary resuscitation. Should we use it? A randomized pilot study

Abstract: inTroducTion: Sudden cardiac arrest is a challenge for medical personnel as well as a high socioeconomic burden. Many authors indicate that the quality of cardiopulmonary resuscitation, including chest compressions performed without an assisted device, may raise doubts due to failure to achieve the value of chest compressions recommended by the guidelines of the American Cardiac Society. All kinds of devices supporting cardiopulmonary resuscitation, including CPR feedback devices, may be helpful in this regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, it is a standard for CPR studies, and the manikins applied in our study are widely used in CPR simulation and research, allowing repetition of resuscitation activities with equal conditions for all cases. [40,41] These seccond limitation is the study group. The results in fact refer to nursing students and not to other medical professions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a standard for CPR studies, and the manikins applied in our study are widely used in CPR simulation and research, allowing repetition of resuscitation activities with equal conditions for all cases. [40,41] These seccond limitation is the study group. The results in fact refer to nursing students and not to other medical professions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 30 31 32 33 34 35 , 74 ] Real-time AVF is one strategy identified by the AHA and ILCOR as a strategy that may improve guideline adherence and IHCA outcomes. [ 27 33 35 ] Simulated studies show improved CPR quality with feedback devices [Tables 2 and 3 ];[ 42 44 45 ], 48 ,, 52 ,[ 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 ] however, the evidence for improvement in clinical outcomes is still very limited [Tables 4 and 5 ]. [ 3 51 73 74 ] That said, these devices have also been shown to be easy to use by both medical professionals and lay persons[ 45 ] and remain an understudied opportunity to improve IHCA outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Stand-alone AVF devices provide benefits in cost and simplicity, making them potentially useful for applications both in-and outside of hospital settings. Despite an abundance of non-randomized and simulation studies [Tables 2 and 3 42 44 45 48 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 ] data from clinical randomized controlled trials (RCT) are sparse [ Table 4 ]. [ 3 51 73 74 ] To date, there have been no < 15 non-AED compression AVF devices have been released to market [ Table 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Independent AVF devices are typically user-friendly, with low technical complexity and production costs, making them suitable for personal or household use. Iskrzycki's experiment demonstrated that the use of visual real-time feedback devices significantly improved the quality of CPR [29], while Majer's study showed that the utilization of TrueCPR devices improved the chest compression parameters in simulated resuscitation scenarios [30].…”
Section: Introductionmentioning
confidence: 99%